The multiple roles of traditional healers in cancer treatment in Malaysia - Sharan Merriam; Mazanah Muhamad (Adult Education Research Conference, 2014)
For a number of reasons ranging from cultural compatibility, to accessibility, to cost, traditional healers are a major source of health care in developing countries. Partially as a result of the widespread practice of visiting traditional healers, cancer diagnosis and treatment in Malaysia is often delayed or interrupted resulting in late presentation, advanced stage diagnosis, and a higher mortality rate than in Western countries. However, there is very little research on the role of traditional healers in cancer treatment in Malaysia. This qualitative study was designed to identify the roles traditional healers play in cancer diagnosis and treatment. To that end, in-depth interviews were conducted with 14 Malay traditional healers, 13 cancer patients who had seen both traditional healers and Western doctors, and 12 cancer medical specialists. Analysis of the data from these 39 participants revealed four roles traditional healers play in cancer treatment—medicinal healer, emotional comforter, spiritual guide, and palliative caregiver. Recognition of these roles by the Western medical system is proposed as a starting point for alleviating the cancer burden in Malaysia.